THE EFFECT OF CAPITAL ADEQUACY RATIO AND NON-PERFORMING LOANS ON LENDING, MODERATED BY INTEREST RATE (An Empirical Study on Commercial Banks Listed on the Indonesia Stock Exchange in 2018–2023) - Kadek Yoni Adristi; I Nyoman Wijana Asmara Putra (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) on loan disbursement, with the interest rate as a moderating variable. The study utilizes data from 29 commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period, with a total of 174 firm-year observations selected using purposive sampling. The analytical method employed is Moderated Regression Analysis (MRA). The results indicate that CAR has a significant negative effect on loan disbursement. Meanwhile, NPL does not have a significant effect on loan disbursement. Furthermore, the interest rate weakens the negative effect of CAR on loan disbursement, and it neither strengthens nor weakens the effect of NPL on loan disbursement.